Potomac interim report to the President - United States.; Potomac River Basin Advisory Committee. ([U.S. Department of the Interior], 1966)
Issued by the Federal Interdepartmental Task Force on the Potomac and the Potomac River Basin Advisory Committee.
Issued by the Federal Interdepartmental Task Force on the Potomac and the Potomac River Basin Advisory Committee.
"January 1966."
Recommendations -- Potomac River watershed -- Cleaning it up -- Water for man's use -- Water & space for man's fulfillment -- Potomac panorama (i.e., a photographic essay) -- A Potomoc essay : A river & a piece of country / John Graves.
Keywords: Water resources development. / fast / (OCoLC)fst01171955; Water / Pollution. / fast / (OCoLC)fst01171279; Water Supply.; Water Pollution.; Recreation.; Water / Pollution / Potomac River Watershed.; Water resources development / Potomac River Watershed.; United States / Potomac River Watershed. / fast / (OCoLC)fst01264895; United States / Potomac River. / fast / (OCoLC)fst01245982; United States.; Potomac River / Pictorial works.; Pictorial works. / fast / (OCoLC)fst01423874